Monitoring SpO2, BPM, and Temperature on Smartband with Data Sending Using IoT Android Display - Mahardika, Melva; Irianto, Bambang Guruh; Wisana, I Dewa Gede Hari; Triwiyanto, Triwiyanto; Rathod, Yagnik (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
No matter if a patient is receiving care at home or in a hospital, monitoring them is an essential part of healthcare.Currently, many hospitals use a manual method to measure body temperature, oxygen saturation, and heart rate, necessitating physical visits from nurses to patients' rooms to get data. This approach, however, turns out to be less effective and time-consuming. This research aims to develop a wearable device placed on a patient's wrist is the main goal of this project. Body temperature, oxygen saturation, and heart rate are the three vital sign metrics that this gadget will be able to continuouslymonitor in real-time. Additionally, Ubidots integration will enable the device to deliver notifications based on the data gathered.The contribution of this research is the development of IoT-based wearable devices for remote monitoring, which aims to improve the quality of health service monitoring. The tool is expected to facilitate remote monitoring for medical personnel and patient families. This research method uses MAX30100 as digital sensors to monitor heart rate, oxygen saturation and MLX90614 as a sensor to detect body temperature. The results of this research can display data on the Ubidots application and send notifications to email. The results showed that the SpO2 sensor had the lowest error rate of 0.2% and the highest mistake rate of 1.6%. The error rates displayed by the BPM sensor varied, with the lowest being 0.6% and the largest being 5.68%. For body temperature measurements, the minimum error rate recorded is 0.002%, while the maximum error rate is 0.016%. This research shows that it is time to develop further into a sophisticated health monitoring tool to improve the quality of health services.